Semantic and Phraseological Characteristics of the Concept of Justice (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article examines the semantic and phraseological characteristics of the concept of justice. The study emphasizes the importance of the concept of justice as a sociophilosophical, moral and legal concept that plays a significant role in the sociopolitical consciousness of people. The author analyzes various interpretations of justice in philosophy, law, morality and politics, paying attention to their historical and socio-economic contexts.